Financial Signals and Firm Value in Indonesia’s SME ‎Acceleration Board: Evidence from Sales Growth, Profitability, ‎and Firm Size - Saraswati, Gita; Suciati, Ranila; Nur Supriadi, Yudi (JPI: Jurnal Pustaka Indonesia, 2026)
This study investigates whether sales growth, profitability, and firm size are associated with firm value among small and medium-sized enterprise issuers listed on the Indonesia Stock Exchange Acceleration Board, a market segment characterized by relatively limited public information and potentially higher information asymmetry. Using a quantitative explanatory design, the study analyzed a balanced panel of 13 issuers observed over the 2022–2024 period, producing 39 firm-year observations. Firm value was measured using Tobin’s Q, sales growth was calculated from annual changes in sales, profitability was proxied by return on assets, and firm size was measured using the natural logarithm of total assets. Panel-model selection procedures supported the use of a pooled ordinary least squares model. The results showed that sales growth and profitability had negative but statistically non-detectable associations with firm value, whereas firm size had a positive but statistically non-detectable association. The predictors were also not jointly significant, and the model demonstrated limited explanatory power. These findings suggest that conventional accounting-based indicators may not function as sufficiently strong standalone signals of market valuation within a small and information-constrained public-equity environment. The study contributes to signaling theory by indicating that the effectiveness of financial signals is context dependent and may be shaped by market characteristics, information credibility, and investors’ capacity to interpret firm-level indicators. The practical implication is that managers, investors, and regulators should complement sales growth, profitability, and firm size with information on disclosure quality, market liquidity, governance, and long-term business prospects when evaluating Acceleration Board issuers.